Ultracompact Optical Comparator for 4-bit QPSK-Modulated Signal Based on Silicon Photonic Waveguide - Yohei Aikawa (IEEE Photonics Journal, 2019)
Optical comparators have the potential to improve the operational speed and power consumption of optical communication systems, as they directly perform the required operations in the optical domain to avoid any optic-electro conversions. Various comparators are optically implemented; however, most studies have been confined to an on–off keying modulation. Although there is a comparator available for the phase-shift keying (PSK) modulation, the device has a limitation that requires integration into an actual system. In this paper, the author provides an optical comparator based on a silicon waveguide for a quadrature PSK (QPSK) signal. The proposed comparator is a simple 2.0 × 0.1 mm $^2$ rectangle, which is approximately 1/7500 the size of comparators from previous studies, and the device mainly comprises a delay line interferometer, a variable splitting ratio optical coupler, and a phase shifter. The performance of the comparator designed for 00 00 and 11 00 codewords was experimentally evaluated. The comparator generates the coupled symbol with the comparison result between the target code and the input signal. The paper demonstrates the feasibility of the ultracompact optical comparator for a 4-bit QPSK-modulated signal at 10 Gbaud.